Correlation of The Chronic Kidney Disease Epidemiology Collaboration Equation With Conventional 24-Hour Urinary Creatinine Clearance Test For Estimating Glomerular Filtration Rate In Chronic Kidney Disease Patients - Qayyum, Ahad; Arif, Ayesha; Asif, Sonia (Pakistan Journal of Kidney Diseases, 2021)
Estimation of GFR helps in assessing extent and progression of renal disease, and adjusting dosage of various drugs. In routine clinical practice, the most common method for assessing GFR is performing a 24-hour urine collection for evaluation of creatinine (an endogenous marker) clearance since tests like Inulin clearance are cumbersome and kept for pure research purpose. Equations like Cockcroft-Gault and MDRD equation are convenient for estimation of GFR, nevertheless the new Chronic Kidney Disease Epidemiology Collaboration Equation (CKD-EPI equation) was introduced and validated to be accurate in estimating GFR. This study was conducted to determine a correlation between GFR calculated by the CKD-EPI and the conventional 24-hour urinary creatinine clearance test in chronic kidney disease patients admitted at a tertiary health care setting. METHODOLOGY A cross sectional survey of 100 adults with chronic kidney disease admitted at Department of Nephrology, Bahria Town Hospital Lahore over a 6-month period were included in the study. A blood sample was taken from the patients on the same day of starting 24-hour urine collection by the researcher. RESULTS The participants had a mean age of 42.18±12.49. There were 58 male and 42 female patients. The correlation between GFR calculated by CKDEPIequation and conventional 24-hour urinary creatinine clearance test and was found to be 0.679 which denotes a positive correlation, P 0.01. CONCLUSION A positive correlation between the estimated GFR calculated by the CKD-EPI equation and conventional 24-hour urinary creatinine clearance test was evident.Hence, CKD-EPI equation is replaceble with 24 urinary CrCl.